How food works - Levy, Joel 1971-; Smith, Ginny (Dorling Kindersley Limited, 2017)
How Food Works is your own friendly nutritionist, on hand to debunk common food myths and give you the answers to those pressing questions with easy-to-swallow information. Today's media is full of new discoveries about food - red wine is good for your heart, caffeine will raise your blood pressure - but is there a biological basis to these claims? How Food Works reveals the facts behind your food, evaluates the benefits of superfoods and antioxidants, and explores behind-the-scenes of modern food production. Delve into the science behind diets including gluten-free and veganism, as well as the benefits of different diets from around the world. Understand what actually makes food organic, how important sell-by dates really are, and how much salt you should actually be eating. Get the answers to dozens more niggling food questions in How Food Works.